2019
DOI: 10.1021/acs.jpcb.8b11892
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aqueous 1-Ethyl-3-Methylimidazolium Ionic Liquids for Calculation of Ion Dissociation

Abstract: We employ precise measuring techniques to determine the densities, viscosities, and ionic conductivities of three aqueous 1-ethyl-3-methylimidazolium [emim]+ ionic liquid (IL) systems with minimal experimental uncertainty. We simultaneously present a novel method for estimating ion dissociation relying only on these three measurements and the estimated Stokes radii of the ions based on the Stokes–Einstein and Nernst–Einstein equations. Ion dissociation values are estimated across a range of IL concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…In this section, we report ion dissociation values calculated using the framework described above and in our previous work. 35 The ion dissociation values at 298.15 and 313.15 K can be found in Table S9 of the Supporting Information. It is important to acknowledge that these values are calculated using fixed Stokes radii calculated using the group contribution method and do not account for changes in temperature or ion concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we report ion dissociation values calculated using the framework described above and in our previous work. 35 The ion dissociation values at 298.15 and 313.15 K can be found in Table S9 of the Supporting Information. It is important to acknowledge that these values are calculated using fixed Stokes radii calculated using the group contribution method and do not account for changes in temperature or ion concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this section, we present a condensed description of our framework used to calculate ion dissociation; a more detailed description of this approach is available in our previous work. , …”
Section: Background and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Nordness et al 26 studied the dissociation of some ILs in aqueous solution. They found that the dissociation fraction ξ has a minimum value at a water mole fraction of 0.98.…”
Section: Ph Values and Dissociation Mechanism Of Thementioning
confidence: 99%